Building DMZs for Enterprise networks - Shimonski, Robert (Rockland, Mass. : Syngress Pub., 2003)
This book covers what an administrator needs to plan out and integrate a DMZ into a network for small, medium and Enterprise networks. In most enterprises the perception is that a firewall provides a hardened perimeter. However, the security of internal networks and hosts is usually very soft. In such an environment, a non-DMZ system that is offering services to the Internet creates the opportunity to leapfrog to other hosts in the soft interior of your network. In this scenario your internal network is fair game for any attacker who manages to penetrate your so-called hard perimeter. - There are currently no books written specifically on DMZs - This book will be unique in that it will be the only book that teaches readers how to build a DMZ using all of these products: ISA Server, Check Point NG, Cisco Routers, Sun Servers, and Nokia Security Appliances. - Dr. Thomas W. Shinder is the author of the best-selling book on Microsoft's ISA, Configuring ISA Server 2000. Customers of the first book will certainly buy this book.
Includes index.
Keywords: Computer networks -- Access control; Computer networks -- Security measures; Wide area networks (Computer networks) -- Access; Electronic books